Predicting transformer end of life using transformer thermal life simulation technique - Muftah Saad, Ferass A. (2011)
Large power transformers are key components in power system networks and their correct functioning is vital to system operation. Transformer failures can have enormous impact on security and reliability of supply and cost. In addition, Power transformers ageing are one of the critical issues utilities are facing, since a large number of units are approaching or have exceeded their designed lifetime. Their replacement will involve a considerable amount of time and cost. Therefore, developing a replacement strategy for aged transformer populations is crucial.